Análise de misturas de pigmentos de pinturas policromadas barrocas através de espectroscopia de infravermelho por transformada de Fourier - Hugo Marlon da Silva Nascimento (2019)
One of the areas of study of heritage science is an analysis of samples for the proper characterization of materials and techniques used in works of art; this field requires knowledge in materials, art history and architecture history, conservation and restoration theory and physical-chemical processes. In this paper a methodology for the quantitative analysis of mixtures of pigments on Baroque polychrome paintings was developed. An experimental approach was done, and it is able to provide accurate information about used materials, enabling the development of strategies best suited for conservation and restoration. The methodology was executed by reproducing a baroque tempera recipe, and it was characterized using physical-chemical analysis techniques, such as Fourier Transform Infrared Spectroscopy (FTIR), X Ray Fluorescence (XRF), X Ray Diffraction (XRD) and Scanning Electron Microscopy with Energy Dispersive Spectroscopy. Historically used materials in cultural assets may be of organic or inorganic origin, often in mixtures. In this paper, the Baroque polychrome technique was reproduced using mixtures of colored pigments with white pigment, being the colored ones: blue phenazine from cobalt-zinc silicate ((Co,Zn) 2SiO4) and white pigment zinc oxide (ZnO). To add pigment to the tempera, it was necessary to compound a pigment paste, which was mixed with distilled water to form a paste using a glass crusher. The tempera was accomplished by mixing the pigment paste to two common binder types at the time (linseed oil and egg yolk) as prescribed by Smith (2004). In the results it is possible to verify the overlapping of bands due to the mixtures of the materials and that small fractions of pigmets in the mixtures can be difficult to delect in the FTIR technique. This work presents a discussion about the influence of mixtures of material in the spectra obtained by infrared and makes an analysis of the use of the technique in works of art.